The contribution of improved air quality to reduced cardiovascular mortality: Declines in socioeconomic differences over time. (March 2020) - Wyatt, Lauren H.; Peterson, Geoffrey C.L.; Wade, Timothy J.; Neas, Lucas M.; Rappold, Ana G.
Graphical abstract: Highlights: PM2.5 -related county cardiovascular mortality change varied by socioeconomic level. Counties with the least deprivation had the highest rates of PM2.5 reduction. PM2.5 accounted for 12.5% of mortality reduction in moderately deprived areas. PM2.5 accounted for 9.1% of mortality reduction in more deprived counties. The gap in PM2.5 -attributed reductions in CMR was reduced over time. Abstract: Major improvements in air quality since 1990, observed through reductions in fine particulate matter (PM2.5 ), have been associated with reduced cardiovascular mortality rates (CMR). However, it is not well understood whether the health benefit attributed to PM2.5 reductions has been similar across strata of socioeconomic deprivation (SED). Using mixed effect regression models, we estimated the PM2.5 -related change in the CMR across 2, 132 US counties in five SED strata between 1990 and 2010. The analysis included annual county CMR (deaths/100, 000 person-year), annual county PM2.5 (μg/m 3 ), and an index of county SED based on socioeconomic factors from the 1990 US Census. The contribution of PM2.5 reductions to decreased CMR varied by SED strata and over time. Yearly differences resulted from varying rates of PM2.5 reduction and because of the non-linear relationship between CMR and PM2.5 concentration. In early years, PM2.5 -related CMR reductions were smallest in the most deprived counties compared to all other counties (range: 0.4–0.6 vs 0.7–1.6 fewer deaths/100, 000 person-year), due to slower rates of PM2.5 reduction in these counties. However, in later years, PM2.5 -related CMR reductions were highest counties with moderate to high deprivation, compared to counties with the least deprivation (range: 1.0–2.2 vs 0.5–0.9 fewer deaths/100, 000 person-year) due to larger CMR reductions per decrease in PM2.5 . We identified that CMR reductions related to air quality improvements have become more similar over time between socioeconomic strata.